1976
DOI: 10.1146/annurev.bi.45.070176.001441
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Diaminobutane (Putrescine), Spermidine, and Spermine

Abstract: As is evident from the above summary of the recent literature, plus many other papers not cited here, there is an extensive literature indicating the physiological significance of these amines. The most important studies can be summarized as follows. (a) Polyamines and their biosynthetic enzymes are ubiquitous. (b) Microbiological mutants have been described in which there is a definite requirement of polyamines for growth. (c) The concentration of polyamines and their biosynthesis enzymes increase when the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
446
1
12

Year Published

1978
1978
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,183 publications
(471 citation statements)
references
References 0 publications
12
446
1
12
Order By: Relevance
“…The other pathway, which is the most relevant quantitatively, involves the transfer of the propylamine moiety from the decarboxylated S-adenosylmethionine to putrescine or spermidine (Pegg& Williams-Ashman, 1970;Bowman et al, 1973;Tabor & Tabor, 1976;Zappia et al, 1977a): 2mol of 5'-methylthioadenosine is released/mol of spermine and 1 mol/mol of spermidine. Both enzymic routes are virtually irreversible.…”
mentioning
confidence: 99%
“…The other pathway, which is the most relevant quantitatively, involves the transfer of the propylamine moiety from the decarboxylated S-adenosylmethionine to putrescine or spermidine (Pegg& Williams-Ashman, 1970;Bowman et al, 1973;Tabor & Tabor, 1976;Zappia et al, 1977a): 2mol of 5'-methylthioadenosine is released/mol of spermine and 1 mol/mol of spermidine. Both enzymic routes are virtually irreversible.…”
mentioning
confidence: 99%
“…Acrolein is a well-known cytotoxin that is widely distributed in biological material (9). In an early study Willmer and Walersteiner (10) showed that various aldehydes inhibited growth and cellular activity in the concentration region of 2 mM.…”
Section: Discussionmentioning
confidence: 99%
“…This change in enzyme stability may lead to an apparent increase in activity, even when the rate of enzyme synthesis remains constant (Tabor & Tabor, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The naturally occurring polyamines spermine and spermidine and the diamine putrescine are widely distributed in biological material (Cohen, 1971;Bachrach, 1973) and are currently considered to play an important role in regulating growth, development and function of various types of cells (Caldarera & Moruzzi, 1970;Heby et al, 1975a;Tabor & Tabor, 1976;Janne et al, 1978). Small changes in growth rates, progression through the mitotic cycle and responses to various hormones are frequently accompanied by striking alterations in the activity of the biosynthetic enzymes (Russell et al, 1976;CIo et al, 1976).…”
mentioning
confidence: 99%